2019
DOI: 10.3390/s19081889
|View full text |Cite
|
Sign up to set email alerts
|

Visual Navigation for Recovering an AUV by Another AUV in Shallow Water

Abstract: Autonomous underwater vehicles (AUVs) play very important roles in underwater missions. However, the reliability of the automated recovery of AUVs has still not been well addressed. We propose a vision-based framework for automatically recovering an AUV by another AUV in shallow water. The proposed framework contains a detection phase for the robust detection of underwater landmarks mounted on the docking station in shallow water and a pose-estimation phase for estimating the pose between AUVs and underwater l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…An experiment using a ship model has been conducted in a laboratory to evaluate the feasibility of the algorithm. The test results demonstrated that the average localization error is approximately 5 cm and the average relative location error is approximately 2% in the range of 3.6 m. A similar approach was proposed by Liu et al [71]. A vision-based framework for automatically recovering an AUV by another AUV in shallow water was presented in this work.…”
Section: Optical Navigationmentioning
confidence: 68%
“…An experiment using a ship model has been conducted in a laboratory to evaluate the feasibility of the algorithm. The test results demonstrated that the average localization error is approximately 5 cm and the average relative location error is approximately 2% in the range of 3.6 m. A similar approach was proposed by Liu et al [71]. A vision-based framework for automatically recovering an AUV by another AUV in shallow water was presented in this work.…”
Section: Optical Navigationmentioning
confidence: 68%
“…The guidance feature extraction was carried out using the method proposed in this study, and the PPARD estimation results are presented in Table 2. 22) in shallow-water field experiments using the lamps and docking station deployed in [14]. The SIA-3 AUV had a diameter of 384 mm, a length of 5486 mm, and a weight of 1500 kg in air.…”
Section: Comparison Of Proposed Methods and Oi Methodsmentioning
confidence: 99%
“…Image segmentation is mainly used to segment guidance lamp regions to extract the guidance features. The processing methods, here, include the mean-shift algorithm [11], region growing method [12], and deep learning [13,14]. Guidance feature extraction can be divided into two types, namely guidance feature extraction based on image binarization (GFEBIB) and guided feature extraction based on edge detection (GFEBED).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a TMS suspended from a surface platform such as a surface vessel, presents a highly dynamic system, with wave height and period dictating the viability of launch and recovery operations [16].Although docking of UUVs to a moving docking station is reported, the research is mainly focused on an AUV docking and on compensation of disturbances in the horizontal plane (e.g., cross-current), while assuming minimal docking station heave oscillations. Recovering of an AUV by another AUV in shallow water is presented in [17]. The system consists of a "mother" AUV with a funnel shaped docking station attached to its body, designed to accommodate launch and recovery of the "daughter" AUV.…”
mentioning
confidence: 99%